Role of secretomes in chronic wound treatment: a review - Limanda, Claudia Felicia; Intizam, Marwa Humaira; Augustin, Dara Cynthia (Bali Dermatology Venereology and Aesthetic Journal, 2024)
Living with a chronic wound may prove to be devastating to patients both physically and psychologically. Wound increases economic and society burden due to low healing rate, prolonged hospital treatment, and increased epidemiology worldwide. Therefore, application wound treatment modalities are necessary for patient recovery. However, each modality has their own advantage and limitation. As a newly-founded modality, secretome, which originated from Mesenchymal stem cells (MSCs) plays an important role in chronic wound healing due to its ability in promoting tissue regeneration and self-renewal that supports cell proliferation and migration. However, different therapeutic potentials can arise according to each source of stem cells. This review highlights the importance of secretome as a modality in treating chronic wounds. Secretome types, stem cell origin, and results when applied in vitro and in vivo will also be comprehensively reviewed.